A case report of H‐syndrome from Baghdad Medical City treated with tocilizumab. Issue 12 (19th December 2022) - Awadh, Nabaa Ihsan; Gorial, Faiq I.; Hashim, Hashim Talib; Al‐Obaidi, Ahmed Dheyaa; Al‐Obaidi, Mustafa Najah; AlNoori, Ali H.; Aljanabi, Wesal K.
Abstract: This case report presents the first H‐syndrome rarity in Iraq, a 12‐year‐old female patient who was attending the Rheumatology out clinic for progressive hands joint deformities. She has a history of a multi‐systemic collection of diseases with various clinical features that include beta thalassemia minor, sensorineural deafness, and celiac disease. Abstract : H syndrome, also known as histiocytosis‐lymphadenopathy plus syndrome or PHID, is a rare genetic condition caused by mutations in the SLC29A3 gene. This case report presents the first H‐syndrome rarity in Iraq.